2008
DOI: 10.5172/conu.673.28.1-2.37
|View full text |Cite
|
Sign up to set email alerts
|

Cultural competency of graduating US Bachelor of Science nursing students

Abstract: Cultural competence in the delivery of nursing care is an expectation of accreditation and approval boards for nursing in the United States. This study evaluated the effectiveness of four different nursing program curricula in developing culturally competent new graduates. Four methodologically and geographically diverse groups of graduating BSN students in the United States were given the Inventory for Assessing the Process of Cultural Competency Among Healthcare Professionals-Revised (IAPCC-R prior to gradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 15 publications
6
66
1
1
Order By: Relevance
“…Studies in other disciplines also show first-year students may demonstrate higher scores in some perceived dimensions of cultural competence. 43,44 Currently at the study institution, more structured and overt content on issues of cultural awareness and cultural sensitivity is provided during the first professional year, including pedagogies of culturally relevant teaching (ie, use of students' culture[s] as a means to enhance learning 45 ). It is possible that scores on this domain decreased in the P2 and P3 years as pharmacy students gained more experience and realization of what they did and did not know regarding serving diverse patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other disciplines also show first-year students may demonstrate higher scores in some perceived dimensions of cultural competence. 43,44 Currently at the study institution, more structured and overt content on issues of cultural awareness and cultural sensitivity is provided during the first professional year, including pedagogies of culturally relevant teaching (ie, use of students' culture[s] as a means to enhance learning 45 ). It is possible that scores on this domain decreased in the P2 and P3 years as pharmacy students gained more experience and realization of what they did and did not know regarding serving diverse patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings impact nursing curriculum planning in including cultural immersion experiences in the curriculum, and are congruent with other findings in the literature. [11,[41][42][43][44][45][46][56][57][58][59][60][61][62][63][64] Given the importance of cultural immersion in promoting cultural competence among nursing students denoted in the literature, nursing faculty need to consider incorporating cultural immersion in the curriculum through strategic curriculum planning while remaining cognizant of available resources. Study abroad experiences are preferable, but require time, resources, and adequately prepared faculty facilitators.…”
Section: Teaching Methodsmentioning
confidence: 99%
“…Some studies that used this model showed its effectiveness in guiding teaching and learning methods, but there is a need for further research identifying predictors of cultural competence. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] Many approaches were noted in the literature related to cultural competence in the curriculum, and are summarized as follows: the need to critically evaluate implementation and evaluation methods of cultural concepts in the curriculum, [4,9,10,12,15,17,38,39] use of a stand-alone course on culture in the curriculum, [22,30] integration of cultural concepts throughout the curriculum, [12,13,40] use of service learning projects and cultural immersion projects to increase cultural competence, [11,12,[41][42][43][44][45][46][47] lack of qualified faculty members to teach cultural concepts, [23,48] need for course material to adapt to the changing learning needs of students, [45] and international collaboration among teaching institutions to teach cultural competence. [6,35,39,49] While the above note...…”
Section: Introductionmentioning
confidence: 99%
“…Additionally societal and cultural patterns must be integrated across the entire nursing school curricula [4]. According to researchers, the specific problem is little research had focused on associate degree-nursing students to determine if a relationship existed between integrated cultural curriculum and the student's level of cultural awareness [2,9].…”
Section: Problemmentioning
confidence: 99%